Identification and Analysis of Potential Hazards in Informatics Practicum Activities - Winata, Rivaldi Andika; Prasetya, Raynaldi Nugraha; Budiman, Ridho Dedy Arief (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2025)
This study aims to identify and analyze potential hazards occurring during Informatics subject practicum activities at SMP Harapan Ananda, as well as to formulate risk mitigation strategies based on occupational safety approaches. The research employed a descriptive qualitative method supported by simple quantitative analysis through the HIRADC framework (Hazard Identification, Risk Assessment, and Determining Control). Data were collected through observation, interviews, documentation, and questionnaires involving teachers, laboratory technicians, and students. The results revealed four main categories of potential hazards: electrical, ergonomic, physical-environmental, and digital (cyber hazards). Electrical hazards were identified as the most dominant risks due to non-standard installation and insufficient maintenance, while ergonomic and environmental hazards were related to improper workstation design, limited ventilation, and inadequate lighting. Moreover, digital hazards such as data security threats and inappropriate internet access were also identified as emerging issues in technology-based learning. Risk mitigation efforts were implemented through the hierarchy of control, including elimination, engineering controls, administrative procedures, and safety education. This study contributes to the development of safety management in computer laboratories at secondary schools and promotes a culture of safety and digital literacy within technology-integrated educational environments.